APA SAJA FAKTOR PENYEBAB TRAUMA FISIK ? LAPORAN SURVEI DI AREA PERTANIAN - Maisyaroh Arista; Eko Prasetya Widianto; Rizeki Dwi Fibriansari; Devi Elisa Dostya Ainul Qoyyimah; Dharmayanti Putri Jaladri (Poltekkes Kemenkes Malang, 2021)
Abstract: Having a job as a farmer doesn't mean you don't have negative risks that can cause pain. Even the farming profession has health risks that tend to vary with the naked eye. The use of pesticides that can lead to poisoning, the use of agricultural tools and machinery which can cause injury, even to the position at work that can cause certain diseases that can interfere with the activities of farmers. Identify the relationship between causal factors and the incidence of occupational illness in the agricultural sector. The research method is a cross sectional method to link the causative factors with the incidence of work related illness in the agricultural area. The survey was conducted on 357 farmers in the working area of the Lumajang Regency Agriculture Service. Ergonomics analysis results, Pearson Chi Square value is 0.004. This value indicates that there is a relationship between ergonomics and the incidence of back pain. The use of pesticides, has a Pearson Chi Square analysis, the value is 0.000. This value indicates that there is a relationship between the use of pesticides and the disease caused such as shortness of breath or eye irritation. While using alsinta, the Pearson Chi Square analysis has a value of 0.000. This value is below 0.05, which means that there is a close relationship between the use of alsinta and the incidence of injuries by farmers. Based on the results above, there are three factors that cause taruma in the agricultural area, namely pesticides, agricultural tools and machinery and ergonomic position errors. So that efforts are needed to anticipate the high risk of occupational diseases in agricultural areas.. Keywords: Agriculture, Farmer, Occupational disease